Langmuir Probe Evaluation of the Plasma Potential in Tokamak Edge Plasma for Non‐Maxwellian EEDF. Issue 3 (April 2014) - Popov, Tsv. K.; Dimitrova, M.; Ivanova, P.; Hasan, E.; Horáček, J.; Dejarnac, R.; Stöckel, J.; Weinzettl, V.; Kovačič, J.
Abstract The First derivative probe technique for a correct evaluation of the plasma potential in the case of non‐Maxwellian EEDF is presented and used to process experimental data from COMPASS tokamak. Results obtained from classical and first derivative techniques are compared and discussed. The first derivative probe technique provides values for the plasma potential in the scrape‐off layer of tokamak plasmas with an accuracy of about ±10%. Classical probe technique can provide values of the plasma potential only, if the electron and ion temperatures are known as well as the coefficient of secondary electron emission. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)